False positive testing for sickle hemoglobin in a blood donor with mild erythrocytosis and hemoglobin Geldrop St. Anna. (June 2020) - Dunseth, Craig D.; Schlueter, Annette J.; Knudson, C. Michael
Abstract: Solubility testing for sickle hemoglobin is commonly performed to identify blood suitable for patients with sickle cell disease. A 32-year-old Caucasian male blood donor's unit screened positive for sickle hemoglobin via solublity testing (Streck). As the donor was considered low risk for being positive for hemoglobin S (HbS), he self-referred to hematology for further evaluation. Testing with hemoglobin electrophoresis revealed the patient to be negative for HbS; however, 42 % fetal hemoglobin (HbF) was noted. Since this was higher than typically seen in hereditary persistence of HbF, deoxyribonucleic acid (DNA) sequencing of hemoglobin (Hb) was ordered through a referral laboratory. Hb gene sequencing revealed the patient to be heterozygous for Hb Geldrop St. Anna, a rare Hb variant. This variant has previously been shown to migrate in the HbF region with alkaline electrophoresis. The workup demonstrated that the oxygen dissociation curve was left-shifted consistent with slightly increased oxygen affinity of this variant. The patient's hematocrits (Hct) from his past donations were 53 % and 54 % about two years apart and his Hct at his hematology evaluation was 53 %. This report describes the first case of Hb Geldrop St. Anna in the United States and was associated with a false positive HbS screen. This Hb variant is considered to be benign and has an increased oxygen affinity that is associated with mild erythrocytosis. The donor was allowed to continue donating blood products.